Eksistensi Pujian Himne “Mengikut Yesus Keputusanku” dan Perkembangan Musik Kontemporer pada Liturgi Ibadah Masa Kini - Jhonnedy Kolang Nauli Simatupang (Program Studi Etnomusikologi, Fakultas Ilmu Budaya, Universitas Mulawarman, 2023)
The purpose of this research is to see and provide an understanding of the existence of a hymn in the liturgy of Christian worship today, both hymns and contemporary hymns, and the meaning of the hymn